1998
DOI: 10.2527/1998.7661662x
|View full text |Cite
|
Sign up to set email alerts
|

Induced and synchronized estrus in cattle: dose titration of estradiol benzoate in peripubertal heifers and postpartum cows after treatment with an intravaginal progesterone-releasing insert and prostaglandin F2alpha.

Abstract: Peripubertal beef heifers (n = 57) and postpartum multiparous cows (n = 52) were used to determine the optimal dose of estradiol benzoate (EB) to induce and synchronize estrus after treatment with intravaginal progesterone inserts (IVP4, EAZI-BREED CIDR). All females received an IVP4 for 7 d (d 0 = insertion day) with a 25-mg injection of PGF2alpha (Lutalyse) on d 6. At 24 to 30 h after IVP4 removal, females were randomly assigned to be injected subcutaneously with EB at the following doses: heifers 0, .2, .38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
11

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 21 publications
4
36
1
11
Order By: Relevance
“…In another study Stevenson et al [27] detected only 40% of the cows in oestrus when using a similar synchronisation method. Administration of ODB one day after luteolysis may induce an LH surge and behavioural signs of oestrus in anoestrus cows [28]. Recent studies by Pancarci et al [29] and Stevenson et al [27] found that cows injected with 1 or 0.5 mg of ECP induced an LH surge in lactating dairy cows when given 24 h after a luteolytic dose of PGF 2α .…”
Section: Discussionmentioning
confidence: 99%
“…In another study Stevenson et al [27] detected only 40% of the cows in oestrus when using a similar synchronisation method. Administration of ODB one day after luteolysis may induce an LH surge and behavioural signs of oestrus in anoestrus cows [28]. Recent studies by Pancarci et al [29] and Stevenson et al [27] found that cows injected with 1 or 0.5 mg of ECP induced an LH surge in lactating dairy cows when given 24 h after a luteolytic dose of PGF 2α .…”
Section: Discussionmentioning
confidence: 99%
“…Presence of functional CL at CIDR insertion on d 0 correlated to a higher ovulation rate after CIDR removal on d 21 (with CL; 87.0% vs. without CL; 71.4%, P<0.05), but did not correlate to the conception rate (with CL; 45.2% vs. without CL; 39.0%). Lammoglia et al [9] reported significant differences in conception rates between CL presence (52%) and CL absence (22%) after 7 days of CIDR insertion with PGF 2α injection on d 6 and an additional EB injection at 24-30 hr after CIDR removal. On the other hand, there was another study which revealed no significant difference in pregnancy rates between cows with CL presence or CL absence (54% vs. 54%) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various methods for estrous synchronization have been developed, such as single or double injection of PGF 2α [3], ovsynch program (GnRH -PGF 2α -GnRH) [11,13], and intravaginal progesterone with or without combination of other hormones [4,8,9,14]. Single or double injection of PGF 2α effectively regresses CL and induces estrus when injected into cows after d 5 of estrous cycle.…”
mentioning
confidence: 99%
“…Estradiol benzoate in the absence of progesterone (<1.0 ng/ml) has been shown to induce an LH surge approximately 16 to 24 h after its administration (36). However, EB in the presence of a functional CL or when administered with exogenous progestagens decreases gonadotrophin secretion and induces atresia of the dominant follicle (37).…”
Section: Gpe-d6mentioning
confidence: 99%